Field emission properties of tetrapod-shaped ZnO/TiN point light source with semicircle reflecting anode. (November 2022) - Lai, W.Z.; Huang, X.; Wang, X.F.; Wei, Z.H.; Wang, Q.T.; Sun, L.; Zhang, L.; Ye, X.Y.; Ma, L.A.
Abstract: A novel point light source composed of tetrapod-shaped ZnO/TiN (T-ZnO/TiN) cathode and semi-circular groove reflective anode is demonstrated. The T-ZnO/TiN cathode is fabricated on nickel wire by spraying T-ZnO NRs powder and subsequent sputtering of TiN film. Semicircular reflective anodes with different opening sizes were prepared by wire electro-discharge machine. The field-emission properties of point light sources could be dramatically enhanced under semicircle reflecting anode by decreasing the threshold field from 2.61 to 2.10 V/μm. The point light source of D1500 has an extremely high emission current density of 132.73 mA/cm 2 at 3.53 V/μm. The value of J max is about 2.7 times to that of D3000 (∼47.89 mA/m2 at 4.18 V/μm). Experiments and ANSYS electric field simulation show that the combination of low work function hybrid cathode and semicircular reflective anode structure leads to the increase of local field concentration and the enhancement of field emission characteristics. As far as we know, this point light source with semicircular reflective anode is prepared and applied for the first time. The results show that the point light source structure proposed here can not only effectively reduce the threshold field, but also improve the emission current density and luminescence uniformity. Highlights: A novel point light source composed of Ni wire@T-ZnO/TiN emitters and the semicircular reflective anode was demonstrated. The emitters was fabricated on nickel wire by spraying T-ZnO NRs powder and subsequent sputtering of TiN film. Low turn-on field of 1.63 V/μm and high emission current densities of 132.73 mA/cm 2 was achieved.